2022
DOI: 10.3390/curroncol29080436
|View full text |Cite
|
Sign up to set email alerts
|

Role of Polygenic Risk Score in Cancer Precision Medicine of Non-European Populations: A Systematic Review

Abstract: The development of new screening methods and diagnostic tests for traits, common diseases, and cancer is linked to the advent of precision genomic medicine, in which health care is individually adjusted based on a person’s lifestyle, environmental influences, and genetic variants. Based on genome-wide association study (GWAS) analysis, rapid and continuing progress in the discovery of relevant single nucleotide polymorphisms (SNPs) for traits or complex diseases has increased interest in the potential applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Despite recurrent germline TP53 mutations, no other frequently occurring variants have been reported in international studies ( Cornelius et al 2017 ; Kline et al 2017 ; Taher et al 2019 ; Thomas et al 2021 ; Zhang et al 2021 ). Furthermore, the lack of representation of ancestrally diverse populations in genomic studies, especially admixed populations like the Brazilian, highlights the need for local and global initiatives to bridge this knowledge gap ( Fatumo et al 2022 ; Junior et al 2022 ). Such initiatives are crucial to identify novel variants or genetic profiles that may impact disease outcomes, or therapy decisions, ultimately improving health care for underrepresented populations ( Sirugo et al 2019 ; de Almeida et al 2022 ; Fatumo et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite recurrent germline TP53 mutations, no other frequently occurring variants have been reported in international studies ( Cornelius et al 2017 ; Kline et al 2017 ; Taher et al 2019 ; Thomas et al 2021 ; Zhang et al 2021 ). Furthermore, the lack of representation of ancestrally diverse populations in genomic studies, especially admixed populations like the Brazilian, highlights the need for local and global initiatives to bridge this knowledge gap ( Fatumo et al 2022 ; Junior et al 2022 ). Such initiatives are crucial to identify novel variants or genetic profiles that may impact disease outcomes, or therapy decisions, ultimately improving health care for underrepresented populations ( Sirugo et al 2019 ; de Almeida et al 2022 ; Fatumo et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of PRS in cancer genetics for estimating genetic risk and enabling precision medicine has been highlighted. 9 Polygenic risk score-based genetic screening of patients with CRC could yield more accurate results than the current guidelines. 10 Moreover, applying the concept of PRS to CRC revealed that the cumulative burden of CRC-associated common genetic variants is more strongly associated with early-onset CRC compared with late-onset CRC.…”
Section: Introductionmentioning
confidence: 97%